What drags and drives mobility: Explaining Canada's aggregate migration patterns - David Amirault; Daniel de Munnik; Sarah Miller (Bank of Canada, 2012)
Using census data at the economic region level from 1991 to 2006 and a gravity model framework, this paper examines the factors that influence migration within Canada. Results from both Poisson pseudo-maximum likelihood and negative binominal regression models suggest that provincial borders are statistically significant barriers to migration but the magnitude of their effect varies by model specification. The regression results also indicate that differences in employment rates, household incomes and language are important in explaining migration between Canadian economic regions. We also find evidence that the negative effect of distance on migration may be declining over time.
Keywords: J61; R23; 330; Regional economic developments; Labour markets; Econometric and statistical methods